Leiomyosarcoma of inferior vena cava with intracardiac extension presenting as Budd-Chiari syndrome: Report of a rare case - Kaniyappan Nambiyar; Arvind Ahuja; Minakshi Bhardwaj (Wolters Kluwer Medknow Publications, 2017)
Primary leiomyosarcoma of vascular origin is a rare malignant smooth muscle tumor. This report describes a case of primary leiomyosarcoma of the inferior vena cava (IVC) in a 52-year-old male who presented with complaints of abdominal pain, chest pain, and bilateral lower limb swelling for 4 months. Imaging of the chest and abdomen revealed a mass in the IVC extending into right atrium, heterogeneous enhancement of liver, hepatosplenomegaly, and ascites. Histopathological examination showed a malignant spindle cell tumor with cells arranged in fascicular and hemangiopericytomatous pattern. Immunohistochemistry for smooth muscle actin and desmin confirmed smooth muscle origin of the tumor. Recognition of this tumor in this rare location and Budd-Chiari syndrome-like presentation is imperative for proper management of the patient.